AUDITING BUSINESS MANAGEMENT - Miñano Lecaros, Juan Guillermo (2011)
This article highlights the importance of management control understood as the analysis of efficiency and effectiveness of government institutions and public resources, it’s determined through the evaluation of administrative processes, the use of public performance indicators and performance. The Auditing allows constant growth include increasingly complex problems as motivated by social demands and technology becomes a vital element for management, enabling managers to know how well solve economic and social problems that at this level are presented in the company generating a healthy dynamic. Audit of management or any management control system, has tools that are helpful for entities, so here it will be determined the important of each one of them: Scorecards, indicators, benchmarking, integrated control, etc…